The impact of electronic promotion on consumer behavior: A study on a sample of customers of the Travel Agency Club Voyages Algérie - Boukamoum, Madiha; Charrad, Yacine (The International tax journal, 2025)
This study aimed to examine the impact of electronic promotion on consumer behavior from the perspective of a sample of customers of the travel agency Club Voyages Algérie. Specifically, the study sought to determine the effect of each element of electronic promotion on consumer behavior, as outlined in the study model. To achieve the study’s objectives, a questionnaire was selected as the data collection tool and was distributed to a sample of 100 customers of the travel agency under study. Some questionnaires were excluded due to being invalid for statistical analysis. The valid responses ultimately allowed for the extraction of a set of findings and recommendations. After conducting statistical analysis, the study concluded that the travel agency under investigation does not implement, or does not give sufficient attention to, the application of electronic promotion and its components. However, its impact on the behavior of the agency’s customers was found to be strong.